Q. 84.8( 4 Votes )
Form the differential equation corresponding to (x – a)2 + (y – b)2 = r2 by eliminating a and b.
(x – a)2 + (y – b)2 = r2 …… (i)
On differentiating with respect to x, we get,
Again, differentiating with respect to x we get,
Put the value of (y – b) obtained in (ii) we get,
Put the value of (x – a) and (y – b) in (i) we get,
Put we get,
⇒ (y’3 + y’)2 + (y’2 + 1)2 = r2y’’2
So, the required differential equation is (y’3 + y’)2 + (y’2 + 1)2 = r2y’’2.
Rate this question :
Solve the differential equation given that whenMathematics - Board Papers
The general solution of ex cosy dx – ex siny dy = 0 is:Mathematics - Exemplar
The differential equation represents:Mathematics - Exemplar
Form the differential equation of the family of parabolas having vertex at the origin and axis along positive y–axis.Mathematics - Board Papers
Solve the differential equationMathematics - Exemplar
Given that and y = 0 when x = 5.
Find the value of x when y = 3.Mathematics - Exemplar
Find the equation of a curve passing through origin and satisfying the differential equationMathematics - Exemplar